Top quark decays in the flavor-dependent $$U(1)_X$$ U ( 1 ) X model - Zhao-feng Ge; Jin-lei Yang (European Physical Journal C: Particles and Fields)
Abstract The branching ratios of the flavor changing top quark decays in the SM are too small to be detected experimentally. Therefore, any observable signal for these processes at the LHC would serve as compelling evidence for new physics. In the flavor-dependent $$U(1)_X$$ U ( 1 ) X model, a newly introduced Higgs singlet interacts directly with the quark sector and mixes with the SM-like Higgs, influencing the $$t→ ch$$ t → c h and $$t→ uh$$ t → u h process. Additionally, the flavor dependence of the $$U(1)_X$$ U ( 1 ) X charge affect the $$t→ cZ$$ t → c Z process. In this work, we investigate these process within the framework of the flavor-dependent $$U(1)_X$$ U ( 1 ) X model. Numerical results indicates that with suitable choices of new physics parameters, the branching ratios of these processes in the flavor-dependent $$U(1)_X$$ U ( 1 ) X model can be significantly enhanced. Specifically, the branching ratios of $$t→ ch$$ t → c h and $$t→ uh$$ t → u h can reach the order of $$10^{-4}$$ 10 - 4 in some chosen parameter spaces, which is close to the current experimental upper limit. This suggests that these processes have significant opportunities to be observed experimentally, and the parameter space of the model will face constraints from the experimental upper bounds.